Digital Influencers, Food and Tourism—A New Model of Open Innovation for Businesses in the Ho.Re.Ca. Sector - Marzia Ingrassia; Claudio Bellia; Chiara Giurdanella; Pietro Columba; Stefania Chironi (Journal of Open Innovation: Technology, Market and Complexity, 2022)
The choice of influencer marketing as an endorser for promoting products and services is becoming a more and more effective communication strategy of open innovation. Their use of social media platforms, such as Instagram, allows them to be reached by millions of followers all over the world. As a response to the economic crisis that affected Italy after the first wave of the COVID-19 pandemic, Chiara Ferragni, one of the most endorsed influencers worldwide, started a communication campaign with the aim to promote Italian food and tourist destinations (cities of art, seaside, ski and countryside locations, thermal baths, museums, galleries, hotels, etc.). This study analyses Chiara Ferragni’s activity and the dynamic of communication she used via her Instagram (IG) profile to enhance Italian tourist destinations and “local food & wine”. Specifically, it measured the contribution of local food used as an evocative factor in the appreciation of a tourist destination and its power in different contexts. Hundreds of posts on the influencer’s IG profile were observed using the netnographic analysis. Subsequently, the AGIL model (Adaption, Goal Attainment, Integration, and Latent pattern maintenance) was applied to measure the main dimensions of this communication campaign and its effectiveness to relaunch touristic catering sectors. The study offers a new model of open innovation for advertising and promoting food and catering businesses.